PKM USAHA PANGAN LOKAL PEMBUATAN KERIPIK TEMPE - Boy Rollastin; Zaldy Kurniawan (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Snacks are the lifeblood of the Home Industry Community (IKM), which is still developing. One of the potential producers of local food as a typical Bangka snack is in the northern part of Bangka Island, Belinyu District, Bangka Regency. Bukit Ketok Village in Belinyu District is a granary that produces snacks. One of the home industries that produces various snacks in the form of chips made from tempeh is being developed. This tempe chip product is produced by manual slicing of tempeh using a knife, so the results are less productive and not optimal because it requires a lot of energy and time. In addition, education and innovation are needed to increase their production capacity. Therefore, we need an appropriate technology machine capable of slicing tempe with the desired thickness and uniform size with a semi-automatic slicing system with a processing capability of 10kg/hour. The method used is the procurement of a tempe slicing machine, training on machine operation and machine maintenance. Thus, the training can be easily understood by partners properly and correctly. After that, evaluation and monitoring are carried out to partners so that the level of success of the production process can be measured. The output targets resulting from this community service are media publications, production machines and increased partner production.